The Pan-ErbB tyrosine kinase inhibitor afatinib inhibits multiple steps of the mammarenavirus life cycle - Mizuma, Keita; Takashima, Ayako; Cubitt, Beatrice; de la Torre, Juan C.; Iwasaki, Masaharu (Virology, 2022)
The mammarenavirus Lassa virus (LASV) causes a life-threatening acute febrile disease, Lassa fever (LF). To date, no US Food and Drug Administration (FDA)-licensed medical countermeasures against LASV are available. This underscores the need for the development of novel anti-LASV drugs. Here, we screen an FDA-approved drug library to identify novel anti-LASV drug candidates using an infectious-free cell line expressing a functional LASV ribonucleoprotein (vRNP), where levels of vRNP-directed reporter gene expression serve as a surrogate for vRNP activity. Our screen identified the pan-ErbB tyrosine kinase inhibitor afatinib as a potent inhibitor of LASV vRNP activity. Afatinib inhibited multiplication of lymphocytic choriomeningitis virus (LCMV) a mammarenavirus closely related to LASV. Cell-based assays revealed that afatinib inhibited multiple steps of the LASV and LCMV life cycles. Afatinib also inhibited multiplication of Junín virus vaccine strain Candid#1, indicating that afatinib can have antiviral activity against a broad range of human pathogenic mammarenaviruses. •LASV RNP-expressing cell-based screening against a US FDA-approved drug library.•Pan-ErbB tyrosine kinase inhibitor afatinib is a potent inhibitor of LASV RNP.•Afatinib inhibits multiplication of LCMV and Junín virus (JUNV).•Afatinib inhibits multiple steps of the life cycles of LASV, LCMV, and JUNV.